1980
DOI: 10.1159/000163007
|View full text |Cite
|
Sign up to set email alerts
|

A Correlated Thin Section and Freeze-Fracture Study of <i>o</i>-Phenylphenol-Induced Alterations in the Rat Liver

Abstract: The ultrastructural changes in the liver cells of male Wistar rats induced by oral and subcutaneous application of o-phenylphenol were studied electron microscopically using the thin section and freeze-fracture technique. The rats were given the o-phenylphenol once at a dose of 2,500 mg/kg b.w. and were sacrificed 60 h after treatment. In the orally treated animals, alterations in the nuclei and nucleoli of the hepatocytes were the most prominent alterations. Furthermore, an increase in smooth endoplasmic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These alterations, which are not typical for PAHs, are induced by a variety of substances toxic to the liver [13][14][15][16][17]. The authors have determined that increased blood flow to the liver combined with the effects of the toxic substance causes cellular contacts to loosen in defined areas.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations, which are not typical for PAHs, are induced by a variety of substances toxic to the liver [13][14][15][16][17]. The authors have determined that increased blood flow to the liver combined with the effects of the toxic substance causes cellular contacts to loosen in defined areas.…”
Section: Discussionmentioning
confidence: 99%
“…After initial formation, LDs retain a functional connectivity with the ER, as manifested by their dynamic cargo exchange (Jacquier et al, 2011). Furthermore, live cell imaging demonstrated that LDs move in concert with the ER (Targett-Adams et al, 2003;Guimaraes et al, 2015), and electron microscopy (EM) revealed an intimate morphological relationship between the ER and LDs (Robenek et al, 2006;Ohsaki et al, 2008;Wolinski et al, 2011). However, proteins responsible for the maintenance of ER-LD contacts are so far unknown.…”
Section: Introductionmentioning
confidence: 99%